Indigenous Village Autonomy on Forest Resource Management in Padangtegal Indigenous Village - A. A Gede Oka Parwata; Ni Luh Made Dwi Pusparini; A. A. Ayu Ngr. Harmini (Jurnal Hukum Prasada, 2022)
Forests have a function as a life buffer so that community welfare should be maintained responsibly and sustainably. In addition, the forest resources management and community participation, Balinese local wisdom regarding forest protection are based on Wana Kerthi which is part of Sad Kerthi. The concept is also one of Tri Hita Karana's philosophies. The importance of indigenous villages regarding forest management in Bali needs more attention from both the central and local governments. Moreover, the attention is in the forms of clearer regulations, especially the authority boundaries between traditional villages and the government. The purpose of this study is to investigate the forest status in Padangtegal Indigenous Village and to investigate its roles in indigenous forest management. The method used in the study is the empirical legal research method. The results of this study indicated that the status of the forest managed by the Padangtegal Indigenous Village is a 26-hectare indigenous forest that has the main function as a conservation forest based on the Tri Hita Karana philosophy. The role of Padangtegal Traditional Village in forest management is following the Bali Provincial Regulation Number 4 of 2019 concerning Indigenous Villages (hereinafter referred to as the Indigenous Village Regulation), with autonomy owned by the indigenous village to have rights in regulating its household which is stated in the form of awig-awig. Customary forests as indigenous villages’ padruen are used to create the welfare of indigenous village communities.